A BOOK REVIEW OF “CONTERMPORARY CHALLENGES TO EDUCATION IN MEDICINE AT THE UNIVERSITY LEVEL" (DISTANCE AND E-LEARNING) - Diana Dimitrova (Педагогически форум)
Modern challenges to education in medicine at the university level (distance and e-learning) is the name of a book by Associated Proffesor Marinela Ivanova Grudeva and Assoc. Prof. Ivan Stoyanov Merdzhanov and it comes out at a time when business models of management are required in education, the educational system has new a public difference and a generational difference between students and teachers posing serious didactical, organisational and communication deficits. Any thinking person, as a parent, trainer, teacher or observer, understands that today's generation is too different from the preceding one. Technological and digital progress, globalisation, new visions of professionalism are only a part of the educational problems of the XXI century.